Student Perspectives Responding to LGBT viewed in Pancasila Values - Hutapea, Joshua Jofrat Erikogusto; Simarmata, Rendi Rianto; Hasibuan, Ira Febriani (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
LGBT is term for Lesbian, Gay, Bisexual, and Transgender. LGBT is a sexual orientation sexual orientation that is considered abnormal in Indonesian society, because it is not in accordance with the in accordance with the rules of the norms that apply in society. Type of research type of research used is Qualitative research with the method of data collection used is a questionnaire. used is a questionnaire. Pancasila as the basis of the nation's worldview has an important role in life in society. Therefore, students as part of society is at the forefront of the nation's progress. This research aims to explore and understand the views and attitudes of students towards the LGBT community, this is important because students are often considered as agents of change in society. Assessing whether there is harmony or conflict between students' perspectives on LGBT with the values of Pancasila. values of Pancasila.